County map of Nova Scotia, New Brunswick, Cape Breton Id., and Pr. Edward's Id. - Mitchell, S. Augustus (Samuel Augustus), 1792-1868 (S. Augustus Mitchell, Jr., 1872)
Shows counties, cities, proposed and existing railroads, canals, lakes, and rivers; street layout, major roads, and public institutions for Halifax and islands and shoreline detail for Halifax Harbor. Inset: "City and Harbor of Halifax." Relief shown by hachures. Scale [ca. 1:2,900,000].